Analysis of Land Rights Acquisition Through Inheritance in Cases of Customary Land Disputes - Suryana, Ilham Adi; Djajaputera, Gunawan (Faculty of Law, Universitas Pekalongan, 2024)
This study focuses on analyzing the interaction between formal inheritance law and customary law in the context of acquiring land rights through inheritance, particularly in cases of customary land disputes in Indonesia. Through literature review and case analysis, this research evaluates how formal inheritance law, represented by the Civil Code, and local customary legal practices can conflict, causing complexity and disputes in the transmission of land rights. The main findings indicate that the misalignment between these two legal systems often results in injustices in the distribution of inheritance and prolonged disputes. This study proposes the need for legal reform that integrates customary law with national law, supporting the recording and codification of customary law to ensure justice and legal certainty, as well as respecting the cultural values of indigenous communities. The research concludes by recommending the development of more inclusive and sustainable policies to effectively manage customary land inheritance in Indonesia